Upland rice-based cropping systems with conservation agriculture in Ivory Coast - CGIAR Research Program on Rice (2021)
A cropping system experiment was conducted at the AfricaRice MBe station over 2015 to 2021. Optimum sowing window and improved cropping system options were identified. Manuscript is under review in Field Crops Res.